Pluripotent Stem Cells for the Study of CNS Development - Petros, Timothy J.; Tyson, Jennifer A.; Anderson, Stewart A. (Frontiers in Molecular Neuroscience, 2011)
The mammalian central nervous system is a complex neuronal meshwork consisting of a diverse array of cellular subtypes generated in a precise spatial and temporal pattern throughout development. Achieving a greater understanding of the molecular and genetic mechanisms that direct a relatively uniform population of neuroepithelial progenitors into the diverse neuronal subtypes remains a significant challenge. A firmer knowledge of the fundamental aspects of developmental neuroscience will allow us to better study the vast array of neurodevelopmental diseases. The advent of stem cell technologies has expedited our ability to generate and isolate populations of distinct interneuron subtypes. To date, researchers have successfully developed protocols to derive many types of neural cells from pluripotent stem cells, with varying degrees of efficiencies and reproducibility. The stem cell field is devoted to the potential of stem cell-derived neurons for the treatment of disease, highlighted by the ability to create patient specific induced pluripotent stem cells. However, another application that is often overlooked is the use of stem cell technology for studying normal neural development. This is especially important for human neurodevelopment, since obtaining embryonic tissue presents numerous technical and ethical challenges. In this review, we will explore the use of pluripotent stem cells for the study of neural development. We will review the different classes of pluripotent stem cells and focus on the types of neurodevelopmental questions that stem cell technologies can help address. In addition to covering the different neural cells derived from stem cells to date, we will detail the derivation and characterization of three of the more thoroughly studied cell groups. We hope that this review encourages researchers to develop innovative strategies for using pluripotent stem cells for the study of mammalian, and specifically human, neurodevelopment.